Technical and Economic Evaluation of «Electric House» Project: Investigation of Possibility to Use Electric Power as Single Energy Carrier in Residential Buildings - M. M. Oleshkevich; Y. V. Makosko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers special features of the «Electric House» project where the building is provided with electric power, cold water and sewerage system. The «Electric House» is characterized by ecological cleanness, high reliability in power supply and low capital costs. While running the «Electric House» an annual expenditure of equivalent fuel is increased due to low efficiency of electric power generation at power plants. The profit obtained due to «Electric House» construction is depleted within some period of time. Term of profit depletion is rather high and it is not less than 15 years.